Morphological characterization and transcriptome analysis of leaf angle mutant bhlh112 in maize [Zea mays L.] - Zhang, Yunfang; Ji, Xiangzhuo; Xian, Jinhong; Wang, Yinxia; Peng, Yunling (Frontiers in Plant Science, 2022)
Leaf angle is an important agronomic trait in maize [Zea mays L.]. The compact plant phenotype, with a smaller leaf angle, is suited for high-density planting and thus for increasing crop yields. Here, we studied the ethyl methane sulfonate (EMS)-induced mutant bhlh112. Leaf angle and plant height were significantly decreased in bhlh112 compared to the wild-type plants. After treatment of seedlings with exogenous IAA and ABA respectively, under the optimal concentration of exogenous hormones, the variation of leaf angle of the mutant was more obvious than that of the wild-type, which indicated that the mutant was more sensitive to exogenous hormones. Transcriptome analysis showed that the ZmbHLH112 gene was related to the biosynthesis of auxin and brassinosteroids, and involved in the activation of genes related to the auxin and brassinosteroid signal pathways as well as cell elongation. Among the GO enrichment terms, we found many differentially expressed genes (DEGs) enriched in the cell membrane and ribosomal biosynthesis, hormone biosynthesis and signaling pathways, and flavonoid biosynthesis, which could influence cell growth and the level of endogenous hormones affecting leaf angle. Therefore, ZmbHLH112 might regulate leaf angle development through the auxin signaling and the brassinosteroid biosynthesis pathways. 12 genes related to the development of leaf were screened by WGCNA; In GO enrichment and KEGG pathways, the genes were mainly enriched in rRNA binding, ribosome biogenesis, Structural constituent of ribosome; Arabidopsis ribosome RNA methyltransferase CMAL is involved in plant development, likely by modulating auxin derived signaling pathways; The free 60s ribosomes and polysomes in the functional defective mutant rice minute-like1 (rml1) were significantly reduced, resulting in plant phenotypic diminution, narrow leaves, and growth retardation; Hence, ribosomal subunits may play an important role in leaf development. These results provide a foundation for further elucidation of the molecular mechanism of the regulation of leaf angle in maize.